Tychobythinus antojandro sp. nov., a new troglobitic species of Pselaphinae (Coleoptera: Staphylinidae) from Andalusia, Spain - Hernando, Carles; Pérez, Toni (Zootaxa, 2023)
A new troglobitic species of the subfamily Pselaphinae (Coleoptera: Staphylinidae), Tychobythinus antojandro sp. nov., is described from a cave in south Spain. The main diagnostic features based on male and female specimens are listed and illustrated. The new species shows evident adaptations to cave life, such as reduced eyes with only three ommatidia; reddish-brown in colour; absence of hind wings; and elongate legs and antennae. It can be easily separated from the rest of the Iberian species by the different shape of the aedeagus. So far, Tychobythinus antojandro sp. nov. is known only from its type locality, the limestone cave G.E.V.-2 in the Sierra de Cazorla in southern Spain.